Developing a sustainable development model in Banyumas Regency: Challenges, Opportunities and Global Cooperation Network - Fitrah Elpeni; Kartika Bintarsari Nuriyeni; Sabhita Kusuma Ayusia; Adi Setyorini Fitri; Darmawan Arif; Asma Nailah Afifah; Mokhamad Luthfi Raden (E3S Web of Conferences)
This study investigates the formulation of a sustainable development model in Banyumas Regency, Indonesia, an area with Sustainable Development Goal (SDG) 8, which focuses on promoting inclusive and sustainable economic growth, employment, and decent work for all. The research uses mixed techniques to analyse obstacles, possibilities, and global collaboration networks, comprehensively examining the dynamics of sustainable development in the region. The report delineates economic concerns, including resource scarcity and unequal distribution; environmental issues, such as land degradation and the impacts of climate change; and social challenges, encompassing healthcare accessibility and educational inequalities. Notwithstanding these challenges, Banyumas exhibits considerable potential for sustainable development, with ample natural resources, a cooperative local government, and vigorous community involvement. The study highlights the essential function of global cooperation networks in facilitating sustainable development initiatives via collaboration with international organisations, information exchange, and access to worldwide resources. This enhances comprehension of local, sustainable development dynamics and underscores the significance of cross-border cooperation. The findings seek to guide strategic policy initiatives that tackle current issues while leveraging potential opportunities, fostering a comprehensive and equitable approach to sustainable development in Banyumas that may serve as a paradigm for other swiftly developing areas.